The Relationship of Career Women to Children's Development - Roganda Simanjuntak (Minsight: Midwifery Insight and Innovation Journal, 2025)
Baby's brain growth is influenced by environmental factors including stimulation and parental care. Growth and development is said to be late if a child does not reach the expected stages of growth and development at the proper age. Research conducted at the posyandu in Asano Village, Abepura District, Jayapura City, recorded that 48.75% of children experienced developmental delays. The aim is to identify career women (employees) at the posyandu in Asano Village, Abepura subdistrict, Jayapura City. To identify the development of children with Career Women at the posyandu in Asano Village, Abepura District, Jayapura City. To analyze the relationship between career women (employees) and child development in the posyandu in Asano Village, Abepura subdistrict, Jayapura City. This research method is qualitative with a correlation design with a cross-sectional approach. The sample in this study was 80 people. The sampling technique uses total sampling technique. And the data analysis used is spearman rank. The time spent by career women (employees) with their children at the posyandu in Asano Village, Abepura subdistrict, Jayapura City is mostly <7 hours. The development of children in the posyandu in Asano Village, Abepura District, Jayapura City is mostly P (successful). There is a relationship between career women (employees) and child development at the posyandu in Asano Village, Abepura subdistrict, Jayapura City.